The Relationship Between Locus is of Control External Consumption by Behavior in Adolescent Girls Senior Year - Kusumastuti, Dindha Dwi Maharani, Rini Lestari. S,Psi. M,Si (2016)
Behavior consumptive more specifically explain desire to consume goods have not required to excess to reach satisfaction maximum .Behavior consumptive resulting from the of locus is of control external .Teenagers behave consumptive because of the influence of from friends and its environment be held in order lifestyle and style of dress , teenagers fear that they will excommunicated , or is regarded as teenagers that are outdated , this is in line with the nature of the teens who is in want to know and interested to do the act of trying . The purpose of this research is to know the relationship between locus is of control external with the behavior consumption in adolescent girls senior year .Research methodology this is quantitative with the subject of 80 college student .Data collection method use psychological scale , namely scale locus is of control external and scale of behavior consumption , with the methods incidental sampling .The method of analysis data using product moment. The result showed that a correlation coefficient rxy = 0,048 with sig 0,336 ( 0 > 0,05 ) , so in turning hypothesis .This means not a significant relation exists between locus is of control external consumption by behavior in adolescent girls senior year .The locus is of control external consumption of conduct on adolescent girls senior year are being with empirical rerata of 43,81 and rerata hypothetic of 47,5 and behavior in college student consumptive low with empirical rerata of 87,49 and rerata hypothetic of 102,5.